2017
DOI: 10.1039/c6nj03793c
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective hydrogen peroxide oxidation of primary alcohols to aldehydes by a water-soluble and reusable iron(iii) catalyst in pure water at room temperature

Abstract: A novel, water-soluble and reusable FeCl3 catalyst showed high catalytic activity and chemoselectivity in the H2O2-oxidation of primary alcohols into aldehydes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Electron paramagnetic resonance spectra were obtained on a Bruker EPR spectrometer. Ligand L1 , N -methylquinolin-8-amine, 2-(chloromethyl)-1 H -benzo­[ d ]­imidazole, Mn5 , and Mn6 were prepared following previous literature report.…”
Section: Methodsmentioning
confidence: 99%
“…Electron paramagnetic resonance spectra were obtained on a Bruker EPR spectrometer. Ligand L1 , N -methylquinolin-8-amine, 2-(chloromethyl)-1 H -benzo­[ d ]­imidazole, Mn5 , and Mn6 were prepared following previous literature report.…”
Section: Methodsmentioning
confidence: 99%
“…Utilizing H 2 O 2 , the authors demonstrated that aromatic alcohols were oxidized in lower yields due to competing aryl hydroxylation reactions. Duan reported chemoselective oxidation of primary alcohols to aldehydes by a water‐soluble and reusable iron(III) catalyst utilizing H 2 O 2 as the oxidant under aqueous conditions (entry 12) . The catalyst system was generated in situ from FeCl 3 and an ammonium salt‐functionalized 8‐aminoquinoline 10 .…”
Section: Oxidation Of Alcoholsmentioning
confidence: 99%
“…Additional references cited within the Supporting Information. [31][32][33][34][35][36][37][38][39][40][41]…”
Section: General Experimental Sectionmentioning
confidence: 99%